2017
DOI: 10.31018/jans.v9i2.1338
|View full text |Cite
|
Sign up to set email alerts
|

Effect of planting geometry and training on growth and seed yield of tomato (Solanum lycopersicum L.)

Abstract: The study was conducted to evaluate the effect of planting geometry and training on growth and seed yield of tomato (Solanum lycopersicum L.) using cultivar Solan Lalima during Kharif 2013 at Experimental Farm of Department of Seed Science and Technology, Dr. Y.S. Parmar University of Horticulture and Forestry, Nauni, Solan (H.P.). The treatments comprised of four training levels i.e. Y1 (single stem), Y2 (double stem), Y3 (unpruned with horizontal string) and Y4 (unpruned bush stakes (control)) and eight plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The reason for more number of flower clusters in the plants grown on the raised bed planting system could be the availability of more nutrients because of minimum tillage (Naresh et al, 2012). In case of two stem training system, there would be maximum sunlight penetration and enhanced photosynthetic activity making more assimilates available for flower cluster setting (early shift from vegetative to reproductive phase) as compared to three stem training system, early and higher rate of morphogenesis (cell division, cell differentiation, cell elongation and cell maturation) and also good aeration through the canopy which might be a valid reason to increase the number of flower clusters per plant and ultimately increased fruit set (Ara et al, 2007;Mbonihankuye et al, 2013 andAnsari et al, 2017). Yadav et al (2017) also observed the highest number of fruits per plant (86.59) with a twin stem training technique due to greater levels of carbohydrates and soluble chemicals in the fruits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for more number of flower clusters in the plants grown on the raised bed planting system could be the availability of more nutrients because of minimum tillage (Naresh et al, 2012). In case of two stem training system, there would be maximum sunlight penetration and enhanced photosynthetic activity making more assimilates available for flower cluster setting (early shift from vegetative to reproductive phase) as compared to three stem training system, early and higher rate of morphogenesis (cell division, cell differentiation, cell elongation and cell maturation) and also good aeration through the canopy which might be a valid reason to increase the number of flower clusters per plant and ultimately increased fruit set (Ara et al, 2007;Mbonihankuye et al, 2013 andAnsari et al, 2017). Yadav et al (2017) also observed the highest number of fruits per plant (86.59) with a twin stem training technique due to greater levels of carbohydrates and soluble chemicals in the fruits.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, training and pruning at later phases of plant growth minimises competitors for sunlight and photosynthetic products among fruits. Staking is another key activity that is conducted to make training more effective, especially during the wet season, for enhancing quality, yield, and protecting the crop from assault by soil-borne diseases (Ansari et al, 2017). Furthermore, the typical staking approach causes plants to become more bushy, making it difficult to accommodate a greater number of plants per unit space.…”
Section: Introductionmentioning
confidence: 99%
“…on plants not trained at all (19). According to Ansari, 2012 (2) double stem training system can be recommended for commercial seed production of tomato. In bell pepper, studies by Thakur et al, 2018 (21) revealed maximum fruit weight (175.91 g) and least number of days to first harvest (89.36 days), early flower initiation as well as 50 per cent flowering (52.71 days) under two shoots training level.…”
Section: International Journal Of Current Microbiology and Applied Sciencesmentioning
confidence: 99%